2018
DOI: 10.1111/bju.14481
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes of blue‐light flexible cystoscopy with hexaminolevulinate in the surveillance of bladder cancer: results from a prospective multicentre study

Abstract: Anxiety decreased after BLFC in patients with negative pathology, including patients with false-positive results. Most of the patients undergoing BLFC were willing to pay out of pocket, found the procedure worthwhile and would recommend it to others, irrespective of whether they had a positive BLFC result or whether this was false-positive after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Although PDD has a higher upfront cost, previous studies have found that, due to improved tumor detection and more complete resection, PDD is more cost-effective than WLC in the long term [37,42]. Even in the short term, Smith et al found that patients were willing to pay out-of-pocket despite the increased cost of PDD and demonstrated positive perceptions of PDD regardless of oncologic outcomes [43]. Sievert et al found that the TURB cost for conventional WLC was EUR 1527.11 (USD 2031.06), while PDD had a cost of EUR 1386.83 (USD 1844.48) with a net cost saving of EUR 140.28 (USD 168.57) in a German health system [44].…”
Section: Discussionmentioning
confidence: 99%
“…Although PDD has a higher upfront cost, previous studies have found that, due to improved tumor detection and more complete resection, PDD is more cost-effective than WLC in the long term [37,42]. Even in the short term, Smith et al found that patients were willing to pay out-of-pocket despite the increased cost of PDD and demonstrated positive perceptions of PDD regardless of oncologic outcomes [43]. Sievert et al found that the TURB cost for conventional WLC was EUR 1527.11 (USD 2031.06), while PDD had a cost of EUR 1386.83 (USD 1844.48) with a net cost saving of EUR 140.28 (USD 168.57) in a German health system [44].…”
Section: Discussionmentioning
confidence: 99%
“…1.92)) and postoperating room (1.4 (s.d. 2.13)) 35 . Anxiety decreased uniformly after BLFC (Δ = -2.6), with no differences on the basis of gender, BLFC results (positive or negative) or test performance (false positive or true positive).…”
Section: Patient-reported Outcomesmentioning
confidence: 98%
“…C o n S e n S u S S tat e m e n t baseline, immediately following surveillance cystoscopy and, for those referred to the operating room, after they had received the pathology findings and were aware of their diagnosis 35 . The Patient-Reported Outcomes Measurement Information System (PROMIS) Anxiety 4a form was used to measure anxiety and the PROMIS Pain Intensity 1a form was used to rank pain on a scale from 0 (no pain) to 10 (worst pain).…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, among patients with recurrent disease, blue light cystoscopy identified additional malignant lesions in 46% of patients. These investigators incorporated PRO measures in the trial design, allowing prospective study of satisfaction, anxiety, and willingness to pay among patients undergoing blue light flexible cystoscopy, the results of which were recently published by Smith and colleagues in BJU International (7). In this trial, all patients were administered questionnaires to assess anxiety and pain using validated questionnaires at the initial screening office visit and again immediately following surveillance BLFC.…”
mentioning
confidence: 99%